O ensino de ciências integrado à história das ciências por meio do ensino por investigação - Ferreira, Leonardo Gimenes (2025)
This study focuses on Science Education integrated with the History of Science, using the Inquiry-Based Learning approach. The proposal arose from the desire to make learning more meaningful, bringing students closer to the trajectory of scientists who contributed to the development of science, especially in the Brazilian context. The idea is to create connections between the History of Science and Science Teaching, promoting curiosity, critical thinking and student leadership. The research was developed with high school students from a public school located in the municipality of Santa Helena de Goiás, in the interior of the state of Goiás. The main objective of the work was to develop and apply an Investigative Teaching Sequence (ITS) that would favor the teaching-learning process through the integration of the History of Science and Inquiry-Based Teaching. To make this possible, we outlined the following specific objectives: to identify how the History of Science appears in the documents that guide basic education, seeking to understand its space and educational potential; to apply the ISL with 10th grade students, exploring the trajectory of Brazilian scientists through investigative activities that value the active participation of students; analyze the impacts of this experience on teaching and learning Science, considering both the scientific content and the historical aspects involved. The path taken began with extensive bibliographic research, which provided the theoretical basis for the study. This review was essential to understand the contributions that the History of Science and Inquiry-Based Learning can bring to the classroom, both from a pedagogical and human perspective. Based on this foundation, three articles were written that support and expand the reflection on the proposal: (1) the History of Science in its Historiographical Paths and its Contributions to Science Teaching ; (2) Inquiry- Based Teaching and its Applications in Science Teaching; (3) Investigative Teaching Sequence (ITS) – Inquiry-Based Teaching and its Applications in Science Teaching. The ISL was applied in the classroom with 10th-grade students, promoting rich moments of inquiry, dialogue, exchange of ideas, and discovery. To better understand how students interacted with the proposal, we used the focus group methodology, which allowed us to hear their voices, perceptions, and experiences during the sequence. More than simply transmitting content, this work sought to create an environment in which students felt part of the scientific process, understanding that science is built by real people, in specific historical contexts, with challenges, doubts, and discoveries — just like them, in their learning journey.